Everolimus after failure of one prior VEGF‐targeted therapy in metastatic renal cell carcinoma: Final results of the MARC‐2 trial. Issue 7 (26th October 2020) - Staehler, Michael; Stöckle, Michael; Christoph, Daniel C.; Stenzl, Arnulf; Potthoff, Karin; Grimm, Marc‐Oliver; Klein, Dunja; Harde, Johanna; Brüning, Fabian; Goebell, Peter J.; Augustin, Marinela; Roos, Frederik; et al.
Abstract: MARC‐2, a prospective, multicenter phase IV trial, aimed to investigate clinical outcomes in patients with metastatic renal cell carcinoma (mRCC) treated with everolimus after failure of one initial vascular endothelial growth factor receptor tyrosine kinase inhibitor (VEGFR‐TKI) therapy and to identify subgroups benefiting most, based on clinical characteristics and biomarkers. Patients with clear cell mRCC failing one initial VEGFR‐TKI received everolimus until progression or unacceptable toxicity. Primary endpoint was 6‐month progression‐free survival rate (6moPFS). Secondary endpoints were overall response rate (ORR), PFS, overall survival (OS), and safety. Between 2011 and 2015, 63 patients were enrolled. Median age was 65.4 years (range 43.3‐81.1). 6moPFS was 39.3% (95% confidence interval [CI], 27.0‐51.3) overall, 54.4% (95% CI, 35.2‐70.1) vs 23.7% (95% CI, 10.5‐39.9) for patients aged ≥65 vs <65 years and 51.4% (95% CI, 34.7‐65.7) vs 18.2% (95% CI, 5.7‐36.3) for patients with body mass index (BMI) >25 vs ≤25 kg/m 2 . A Cox proportional hazards model confirmed a longer PFS for patients aged ≥65 years (hazard ratio [HR] 0.46; 95% CI, 0.26‐0.80) and a longer OS for patients with BMI >25 kg/m 2 (HR 0.36; 95% CI, 0.18‐0.71). Median PFS and median OS were 3.8 months (95% CI, 3.2‐6.2) and 16.8 months (95% CI, 14.3‐24.3). ORR was 7.9% and disease control rate was 60.3%. No new safety signals emerged. Most common adverse events were stomatitis (31.7%), fatigue (31.7%), and anemia (30.2%). One patient died from treatment‐related upper gastrointestinal hemorrhage. Everolimus remains a safe and effective treatment option for mRCC patients after one prior VEGFR‐TKI therapy. Patients aged ≥65 years and patients with BMI >25 kg/m 2 benefited most. Abstract : What's new? While different novel treatment options have been approved for the vascular endothelial growth factor receptor tyrosine kinase inhibitor (VEGFR‐TKI) refractory setting in metastatic renal cell carcinoma (mRCC), choosing the optimal second‐line therapy regimen remains a biologic and therapeutic challenge. The MARC‐2 phase IV trial aimed to investigate clinical outcomes in mRCC patients treated with everolimus after failure of one VEGFR‐TKI therapy and to identify subgroups benefiting most. According to the data, everolimus remains a safe and effective treatment option for mRCC patients after one prior VEGFR‐TKI therapy, with the greatest benefit seen in patients ≥65 years or with BMI >25 kg/m 2 .